Shaping ability of three thermally treated nickel‐titanium systems in S‐shaped canals. (3rd March 2021) - Gomaa, Mohamed A.; Osama, Mohammad; Badr, Amany E.
Abstract: This study aimed to compare the shaping ability of ProTaper Next (PTN), HyFlex EDM (HEDM) and One Curve (OC) systems manufactured via different thermal treatment methods in simulated S‐shaped canals. Sixty S‐shaped canals in clear resin blocks were enlarged to a final apical size of 25 using PTN, HEDM and OC instruments ( n  = 20 canals/group). Composite images were obtained by superimposing pre‐ and post‐preparation images. The amount of removed resin was measured perpendicularly to the canal surface in 22 points. Prepared canal width and canal transportation at different levels were determined. Canal aberrations were also recorded. Data were statistically analysed using analysis of variance, the Kruskal–Wallis and the chi‐square tests at a 0.05 significance level. OC produced the most conservative enlargement and better maintained particularly the apical curvature of the S‐shaped canals than HEDM and PTN. OC and HEDM better maintained the canal terminus and coronal curvature than PTN.